PERBANDINGAN EFEKTIVITAS BERKUMUR MENGGUNAKAN LARUTAN PROPOLIS LEBAH 12,38% (APIS MELLIFERA) DAN KLORHEKSIDIN GLUKONAT 0,2 % TERHADAP INDEKS PLAK - Dara Puspita Harvi; Nur Indrawati Lipoeto; Hidayati Hidayati (Faculty of Dentistry Universitas Andalas, 2014)
Dental plaque is the primary etiologic in the development of caries and periodontal disease. Chlorhexidine gluconate 0.2% is the mouthwash that is widely used and effective in reducing dental plaque index, but this mouthwash is chemical with few side effects if used for long periods. Propolis is a bee product that has a high content of flavonoids antibacterial and has many benefits in health and has minimal side effects because it belongs to natural product. This study aims to determine differences in the gargling effectiveness using Chlorhexidine gluconate 0.2% and bee propolis solution 12.38% (Apis mellifera) in reducing dental plaque index. The method used in this research was a clinical experimental with the design of one group pretest and posttest. The subjects consisted of 20 students of MA DR. Abd. Ahmad PGAI Padang. Dental plaque index was measured using PHP plaque index before and after gargling using the solution of bee propolis (Apis mellifera) 12.38% and chlorhexidine gluconate 0.2%. The data of research findings were analyzed using paired T-test (p<0.05). The results show that the mean of plaque index reduction of gargling using the solution of bee propolis 12.38% (Apis mellifera) is 0,88 with the standard deviation of ± 0.66 and the mean of plaque index of gargling using Chlorhexidine gluconate 0. 2% is 1.56 with the standard deviation of ± 0.79. There is a significant difference with p value = 0.005 (p <0.05). Chlorhexidine gluconate 0.2% shows higher reduction, but this mouthwash is the chemical with few side effects, while the solution of bee propolis 12.38% (Apis mellifera) is a natural substance that is safer to use.